Pengaruh Tata Ruang Kantor, Lingkungan Kerja dan Prestasi Kerja Terhadap Semangat Kerja Tenaga Kependidikan di SMKS Krian 2 Sidoarjo - Arifin, Anggi Islamidina; Wulandari, Siti Sri (Universitas Negeri Surabaya, 2021)
This research purpose to determine the effect of office layout, work environment and work performance on the morale of the teaching workforce at Krian 2 Senior High School Sidoarjo. This type of study is a descriptive study with a quantitative approach with multiple linear regression models. The population in this study was the educational staff of Krian 2 Sidoarjo SMKS, which amounted to 57 employees, but researchers only took educational staff whose work was related to administration, this was adjusted to the research objectives. The sample in this study was purposive sampling. Researchers took 50 employees from 57 populations. The results showed that simultaneously the office layout, work environment, and work performance affect work spirit on the morale of the teaching staff at Krian 2 Sidoarjo SMKS, while partially each variable has a significant effect on the morale of the teaching staff at Krian 2 Sidoarjo SMKS